Международный договор и международный обычай как источники международного права интеллектуальной собственности - Абдакимова, Д.А. (Изд-во КарГУ., 2010)
Мақалада зияткерлік меншік жəне оны рəсімдеу тəсілдері саласындағы халықаралық көпшілік ерекшеліктерігі зияткерлік меншікке экстерриториалды-құқықтық əрекеттігі жағынан анықталған. Given item is dedicated to problem of the international agreement and international custom as sources of the right to intellectual property. The Author considers the main theoretical concepts of the sources of the international right. In item is determined that specifics of the sources of the international public right in sphere of the intellectual property and ways of their creation consists in absence экстерриториальности actions of the rights on intellectual property.